Zinc negative electrode with piezoelectric protective layer and preparation method and application thereof

By preparing a piezoelectric protective layer on the zinc negative electrode, using the combination of PLLA and BaTiO3 nanomaterials, the hydrogen evolution reaction, corrosion and other problems of zinc negative electrodes in secondary zinc-based batteries are solved, and more uniform zinc deposition and longer battery cycle life.

CN119495728AActive Publication Date: 2025-02-21NORTHWESTERN POLYTECHNICAL UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411662558.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-21
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The zinc negative electrode has problems such as hydrogen evolution reaction, corrosion, and by-product deposition in secondary zinc-based batteries, resulting in uneven deposition of zinc and uneven electric field distribution, increasing the growth of zinc dendrites and the risk of battery explosion.

Method used

Ester-capped levopolylactic acid (PLLA) was used as the substrate, and BaTiO3 nanomaterial was added, and a piezoelectric protective layer was prepared by electrospinning or spin coating, which was wrapped on the zinc negative electrode to balance the electric field distribution and slow down dendrites' growth.

Benefits of technology

Effectively slows down the growth of zinc dendrites, enhances the cycle life of the battery, reduces the possibility of battery explosion, and improves the stability and electrochemical performance of zinc negative electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495728A_ABST
    Figure CN119495728A_ABST
Patent Text Reader

Abstract

The invention discloses a zinc negative electrode with a piezoelectric protective layer and a preparation method and application of the zinc negative electrode, and relates to the technical field of secondary zinc-based batteries. The method comprises the following steps: dissolving ester-terminated poly-L-lactic acid in a dichloromethane solvent, then adding a DMF (Dimethyl Formamide) solution to promote the conductivity of the solution and a BaTiO3 nano material, and uniformly mixing to obtain a precursor solution; and uniformly applying the precursor solution on a pretreated zinc sheet through an electrostatic spinning method or a spin-coating method, and drying to obtain the piezoelectric protective layer on the pretreated zinc sheet. The BaTiO3 nanoparticles are added into the PLLA substrate, so that the piezoelectric property of the protective layer can be further improved, the electric field distribution on the surface of the zinc negative electrode is further balanced, and the growth of zinc dendrites is slowed down.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of secondary zinc-based batteries, and in particular to a zinc negative electrode with a piezoelectric protective layer, and a preparation method and application thereof. Background Art

[0002] Metallic zinc has a relatively low redox potential (-0.76 V vs. SHE) and a high theoretical capacity (~820 mAh g -1 / ~5855 mAh cm -3 ), and the electrolyte can be water, which has excellent chemical stability, low cost and easy recycling. Metallic zinc is a common negative electrode material for green batteries such as secondary zinc-based batteries such as alkaline zinc-nickel batteries, alkaline zinc-silver batteries, neutral zinc-manganese batteries and zinc-bromine flow batteries. Therefore, improving the stability and electrochemical performance of zinc negative electrodes is the focus of research workers.

[0003] However, the zinc negative electrode still has various unfavorable bottlenecks. First, because the reduction potential of the zinc negative electrode is lower than that of the standard hydrogen electrode, hydrogen evolution reaction will occur when it is in direct contact with the electrolyte. In addition, the inevitable corrosion and by-product deposition will cause uneven zinc deposition, resulting in uneven electric field distribution and aggravated zinc dendrite growth. The generated zinc dendrites will pierce the diaphragm and cause the battery to short-circuit. In addition, the hydrogen generated by the hydrogen evolution reaction will increase the internal pressure of the battery and increase the possibility of battery explosion. Summary of the invention

[0004] In view of the deficiencies in the above-mentioned background technology, the present invention provides a zinc negative electrode with a piezoelectric protective layer, and a preparation method and application thereof. The method uses ester-terminated left-handed polylactic acid (PLLA) as a substrate and BaTiO3 as a filler to prepare a PLLA-based zinc negative electrode protective layer wrapped with BaTiO3 nanofiller by electrospinning or spin coating. The present invention is simple to operate and has a low preparation cost. Adding BaTiO3 nanoparticles to the PLLA substrate can further enhance the piezoelectric properties of the protective layer, thereby balancing the electric field distribution on the surface of the zinc negative electrode and slowing down the growth of zinc dendrites.

[0005] The first object of the present invention is to provide a method for preparing a piezoelectric protective layer, comprising the following steps: The ester-terminated L-polylactic acid is dissolved in a dichloromethane solvent, and then a DMF solution and a BaTiO3 nanomaterial are added and mixed evenly to obtain a precursor solution; The precursor solution is evenly applied on the pretreated zinc sheet by electrostatic spinning or spin coating, and after drying, a piezoelectric protective layer is prepared on the pretreated zinc sheet.

[0006] Preferably, the precursor solution is evenly applied to the pretreated zinc sheet by an electrospinning method, including: using a conductive glue to stick the pretreated zinc sheet to an electrospinning receiving roller, and then electrospinning the precursor solution to obtain a piezoelectric protective layer on the pretreated zinc sheet.

[0007] Preferably, the parameters in the electrospinning process include: the electrospinning syringe needle is connected to the positive electrode, the voltage is 15-20 kV; the receiving roller is connected to the negative electrode, the voltage is -8~-5 kV; The distance between the needle tip and the receiving roller is 10-15 cm, the speed of the receiving roller is 120-150 r / min, the needle head moves left and right 80-120 mm, and the translation speed is 180-250 mm / min; The syringe containing the precursor solution was pushed at a speed of 0.1-0.2 mm / min; During the spinning process, the temperature is maintained at 10-15°C and the humidity is maintained at 20-50%.

[0008] Preferably, when the precursor solution is evenly applied to the pretreated zinc sheet by spin coating, the spin coating parameter is an acceleration of 400-600 r / s. 2 ; The spin coating speed is 1800-2000 r / s; the spin coating time is 20-40s.

[0009] Preferably, the mass concentration of the ester-terminated L-polylactic acid in the precursor solution is 10-15%; the mass concentration of the BaTiO3 nanomaterial in the precursor solution is 5-10%.

[0010] Preferably, the pretreated zinc sheet comprises: grinding and polishing the zinc sheet with sandpaper of 2000, 3000, 5000 and 10000 meshes in sequence, and then cleaning the surface-polished metal zinc with deionized water, ethanol and acetone under ultrasonic conditions, respectively, at a treatment temperature of 20-25°C and a treatment time of 20-40min. After the treatment, drying in a vacuum drying oven at 80-100°C for 5-8h to obtain the pretreated zinc sheet.

[0011] A second object of the present invention is to provide a piezoelectric protective layer.

[0012] The third object of the present invention is to provide an application of a piezoelectric protective layer on a zinc electrode.

[0013] A fourth object of the present invention is to provide a zinc negative electrode with a piezoelectric protective layer, comprising a zinc sheet and a piezoelectric protective layer attached to the zinc sheet.

[0014] A fifth object of the present invention is to provide a zinc negative electrode with a piezoelectric protective layer for use in a secondary zinc-based battery.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a zinc negative electrode with a piezoelectric protective layer and a preparation method and application thereof. The method uses PLLA as a substrate, BaTiO3 nanomaterials as inorganic fillers, and uses electrospinning / spin coating and other methods to prepare a protective layer with piezoelectric properties in one step. The special interaction between PLLA and the zinc sheet is used to ensure the stable existence of the protective layer on the zinc sheet; the high piezoelectricity of the BaTiO3 nanomaterial is used to further improve the piezoelectric output of the protective layer. The present invention is simple to operate and low in cost, and ensures that the PLLA-based zinc negative electrode protective layer containing BaTiO3 nanofillers has a high piezoelectric output, which can effectively balance the internal electric field of the zinc ion battery.

[0016] The PLLA material used in the present invention not only has good hydrophobic properties but also has piezoelectric properties. A layer of PLLA material is coated on the surface of the zinc negative electrode, which can effectively isolate the direct contact between water molecules in the electrolyte and the zinc sheet, so that the corrosion of the electrolyte on the zinc negative electrode can be reduced and the occurrence of side reactions can be slowed down. Although the PLLA material itself has piezoelectric properties, the microstress generated during the deposition and stripping process of the zinc negative electrode is not enough to induce the protective layer to generate a local electric field, so BaTiO3 nanofillers are selected to enhance the piezoelectric effect of the protective layer. In this way, the internal stress generated during the deposition and stripping process of zinc ions can induce the protective layer to generate a local electric field, thereby adjusting the built-in electric field inside the battery, thereby inducing uniform deposition of zinc ions, slowing down the growth of dendrites, and enhancing the cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a flow chart of the preparation method of Example 1 (a) and Example 2 (b) of the method of the present invention.

[0018] Figure 2 These are optical and SEM images of the zinc negative electrode protective layers prepared by Example 1 and Example 2 of the method of the present invention.

[0019] Figure 3 It is the XRD diagram of the zinc negative electrode protective layer prepared by Example 1 and Example 2 of the method of the present invention.

[0020] Figure 4 It is an output performance diagram of the zinc negative electrode protective layer prepared by Example 1 and Example 2 of the method of the present invention.

[0021] Figure 5 1 is the Tafel diagram of the zinc symmetric battery of Example 1, Example 2 and Comparative Example 1 of the method of the present invention.

[0022] Figure 6 It is a relationship diagram between voltage and cycle number of the zinc symmetrical battery of Example 1 of the method of the present invention and Comparative Example 1 under certain current density and capacity conditions. DETAILED DESCRIPTION

[0023] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.

[0024] The present invention is mainly based on two categories: one is to design a three-dimensional framework structure, and the other is surface modification, that is, alloying treatment or coating a protective layer; ferroelectric materials can effectively solve the above problems due to their high dielectric constant and spontaneous polarization performance. First, ferroelectric materials have a large dielectric constant, which can inhibit the formation of a space charge layer, thereby improving the transmission efficiency of zinc ions. Secondly, when a coating containing ferroelectric materials is coated on the zinc negative electrode, a built-in electric field will be generated near the coating. When polarized downward, the direction of the electric field line is from the metal protrusion to the coating surface. Under the action of the electric field, the zinc ions will be transmitted to the bottom of the protrusion, reducing the "tip effect" and thus inhibiting dendrite growth. Considering that ferroelectric materials are usually piezoelectric, they can also regulate ion transport at the electrode by reasonably utilizing volume changes. If piezoelectric materials can be introduced on the substrate, a piezoelectric field (i.e., a piezoelectric effect induced field) will be established under pressure near the electrode surface. That is, when compressive stress is applied to the piezoelectric layer, a piezoelectric field directly from the cathode to the anode will be generated. The established piezoelectric field can be regarded as an ion pump to drive the migration and uniform distribution of ions to the electrode.

[0025] Currently, there are few studies on fully degradable and piezoelectric biomaterials. The present invention selects left-handed polylactic acid (PLLA) with piezoelectric properties, high safety and degradability as the base material of the zinc negative electrode protective layer, and adds BaTiO3 with a high dielectric constant. A left-handed polylactic acid-based zinc negative electrode protective layer containing BaTiO3 nanofiller with piezoelectric properties can be obtained by a one-step method such as electrospinning / spin coating.

[0026] In order to achieve the above object, the present invention provides a first aspect of a method for preparing a piezoelectric protective layer, comprising the following steps: The ester-terminated L-polylactic acid is dissolved in a dichloromethane solvent, and then a DMF solution and a BaTiO3 nanomaterial are added and mixed evenly to obtain a precursor solution; The precursor solution is evenly applied on the pretreated zinc sheet by electrostatic spinning or spin coating, and after drying, a piezoelectric protective layer is prepared on the pretreated zinc sheet.

[0027] Among them, DMF solution is used to promote the conductive properties of the solution.

[0028] The present invention uses a polymer with ferroelectric properties as a zinc negative electrode protective layer, which can not only make good use of the ferroelectric / piezoelectric field brought by the ferroelectric material to regulate the electric field inside the battery, thereby inhibiting the growth of dendrites, but also further prevent direct contact between the electrolyte and the zinc negative electrode, reducing the occurrence of side reactions such as corrosion.

[0029] According to the present invention, the precursor solution is evenly applied to the pretreated zinc sheet by an electrostatic spinning method, including: using a conductive glue to stick the pretreated zinc sheet to an electrostatic spinning receiving roller, and then electrostatically spinning the precursor solution to obtain a piezoelectric protective layer on the pretreated zinc sheet.

[0030] Specifically, the parameters in the electrospinning process include: the electrospinning syringe needle is connected to the positive electrode with a voltage of 15-20 kV; the receiving roller is connected to the negative electrode with a voltage of -8~-5 kV; The distance between the needle tip and the receiving roller is 10-15 cm, the speed of the receiving roller is 120-150 r / min, the needle head moves left and right 80-120 mm, and the translation speed is 180-250 mm / min; The syringe containing the precursor solution was pushed at a speed of 0.1-0.2 mm / min; During the spinning process, the temperature is maintained at 10-15°C and the humidity is maintained at 20-50%.

[0031] According to the present invention, when the precursor solution is evenly applied to the pretreated zinc sheet by spin coating, the spin coating parameters are an acceleration of 400-600 r / s. 2 ; The spin coating speed is 1800-2000 r / s; the spin coating time is 20-40s.

[0032] The mass concentration of the ester-terminated L-polylactic acid in the precursor solution is 10-15%; the mass concentration of the BaTiO3 nanomaterial in the precursor solution is 5-10%. The pre-treated zinc sheet comprises: grinding and polishing the zinc sheet with sandpaper of 2000, 3000, 5000 and 10000 meshes in sequence, and then cleaning the surface-polished metal zinc with deionized water, ethanol and acetone under ultrasonic conditions, respectively, at a treatment temperature of 20-25°C and a treatment time of 20-40 minutes. After the treatment, the zinc sheet is dried in a vacuum drying oven at 80-100°C for 5-8 hours to obtain the pre-treated zinc sheet.

[0033] In one embodiment, a method for preparing a PLLA-based zinc negative electrode protective layer containing BaTiO3 nanofiller by electrospinning comprises the following steps: Step 1, preparation of precursor solution: Weigh 1.2 g of ester-terminated L-polylactic acid (OH-PLLA-COOR, hereinafter referred to as PLLA) and dissolve it in dichloromethane (DCM), stirring for 30 min and ultrasonicating for 20 min three times. After PLLA is fully dissolved until the solution is clear and transparent, add 3 mL of DMF and 0.12 g of BaTiO3 nanomaterials to the mixed solution, stir for 60 min to mix it evenly, and then let it stand to eliminate bubbles in the solution. The whole process is guaranteed to be carried out below 10°C to minimize the volatilization of DCM.

[0034] Step 2: Treatment of zinc sheet: Cut the zinc sheet into 10*12cm size, grind and polish the zinc sheet with 2000, 3000, 5000 and 10000 sandpaper in turn, and then use deionized water, ethanol and acetone to clean the polished metal zinc under ultrasonic conditions, the treatment temperature is 25℃, the treatment time is 30min, and after the treatment, dry it in a vacuum drying oven at 80℃ for 6h to obtain a pure zinc negative electrode. The grinding treatment can not only remove the oxide layer on the surface of the zinc sheet, but also make the surface of the zinc sheet smoother, which is not only conducive to the adhesion of the PLLA layer, but also reduces the possibility of dendrite growth.

[0035] Step 3: Use conductive glue to stick the treated zinc sheet to the receiving roller of electrospinning. Wrap the remaining part of the receiving roller with plastic wrap to avoid contamination. Use the syringe of the electrospinning syringe to absorb 5 mL of PLLA solution. Connect the syringe to the electrospinning needle and place it on the electrospinning machine for spinning to obtain a PLLA-based zinc negative electrode protective layer of BaTiO3 nanofiller.

[0036] Electrospinning parameters: The needle is connected to the positive electrode, the voltage is 17 kV; the receiving roller is connected to the negative electrode, the voltage is -5 kV. The distance between the needle tip and the receiving roller is 12 cm, the speed of the receiving roller is 140 r / min, the needle moves left and right 100 mm, and the translation speed is 200 mm / min. The push speed of the syringe filled with the precursor solution is 0.15 mm / min.

[0037] Spinning environmental parameters: During the spinning process, the temperature was maintained at 10°C and the humidity was 30%.

[0038] Step 4: After spinning is completed, take out the prepared sample and dry it under vacuum at 30°C for 12 hours.

[0039] In one embodiment, a method for preparing a PLLA-based zinc negative electrode protective layer containing BaTiO3 nanofillers by spin coating is used. Step 1: Preparation of precursor solution: Weigh 1.2 g of PLLA, add 10 mL of dichloromethane (DCM) and 0.12 g of BaTiO3 nanomaterials, stir for 3 hours, and then ultrasonicate for 30 minutes to obtain a clear and transparent solution, and then let it stand to eliminate bubbles in the solution. The whole process should be carried out at below 10°C to minimize the volatilization of DCM.

[0040] Step 2: Treatment of zinc sheet: Cut the zinc sheet into 6*6cm size, grind and polish the zinc sheet with 2000, 3000, 5000 and 10000 sandpaper in turn, then use deionized water, ethanol and acetone to clean the polished metal zinc under ultrasonic conditions, the treatment temperature is 25℃, the treatment time is 30min, and after the treatment, dry it in a vacuum drying oven at 80℃ for 6h to obtain a pure zinc negative electrode.

[0041] Step 3: Place the treated zinc sheet on a spin coater for spin coating.

[0042] Spin coating parameters: acceleration is 500 r / s 2 ; The spin coating speed is 2000 r / s; the spin coating time is 30s.

[0043] Step 4: After the spin coating is completed, take out the prepared sample and dry it in a vacuum at 30°C for 12 hours.

[0044] A second aspect of the present invention provides a piezoelectric protective layer.

[0045] A third aspect of the present invention provides an application of a piezoelectric protective layer on a zinc electrode.

[0046] A fourth aspect of the present invention provides a zinc negative electrode with a piezoelectric protective layer, comprising a zinc sheet and a piezoelectric protective layer attached to the zinc sheet.

[0047] A fifth aspect of the present invention provides an application of a zinc negative electrode having a piezoelectric protective layer in a secondary zinc-based battery.

[0048] It should be noted that the experimental methods used in the present invention are all conventional methods unless otherwise specified; the reagents and materials used are all commercially available unless otherwise specified.

[0049] Example 1 See also Figure 1 (a), the preparation method comprises: (1) Weigh 1.2 g of PLLA and dissolve it in DCM. Stir for 30 min and sonicate for 20 min three times. After PLLA is fully dissolved until the solution is clear and transparent, add 3 mL of DMF and 0.12 g of BaTiO3 nanomaterials to the mixed solution, stir for 60 min to mix evenly, and then let the solution stand to eliminate bubbles to obtain a precursor solution. The whole process should be carried out at a temperature below 10 °C to minimize the volatilization of DCM.

[0050] (2) The zinc sheet was cut into a size of 10*12 cm, and was grinded and polished with sandpaper of 2000, 3000, 5000 and 10000 respectively. Then, the surface-polished metal zinc was cleaned with deionized water, ethanol and acetone under ultrasonic conditions. The treatment temperature was 25°C and the treatment time was 30 min. After the treatment, it was dried in a vacuum drying oven at 80°C for 6 h to obtain a pure zinc negative electrode.

[0051] (3) Use conductive glue to stick the treated zinc sheet to the receiving roller of electrospinning. Wrap the remaining part of the receiving roller with plastic wrap to avoid contamination. Use the syringe of the electrospinning syringe to absorb 5 mL of the precursor solution (PLLA solution). Connect the syringe to the electrospinning needle and place it on the electrospinning machine for spinning. Electrospinning parameters: The needle is connected to the positive electrode, the voltage is 17 kV; the receiving roller is connected to the negative electrode, the voltage is -5 kV. The distance between the needle tip and the receiving roller is 12 cm, the speed of the receiving roller is 140 r / min, the needle moves left and right 100 mm, and the translation speed is 200 mm / min. The push speed of the syringe filled with the precursor solution is 0.15 mm / min.

[0052] Spinning environmental parameters: During the spinning process, the temperature was maintained at 10°C and the humidity was 30%.

[0053] After spinning, the prepared sample was removed and dried at 30 °C in a vacuum for 12 h to obtain the PLLA-based zinc negative electrode protective layer (PLLA-BaTiO3@Zn E) of BaTiO3 nanofiller.

[0054] Example 2 See also Figure 1 (b), the preparation method comprises: (1) Weigh 1.2 g of PLLA, add 10 mL of dichloromethane (DCM) and 0.12 g of BaTiO3 nanomaterials, stir for 3 h, and then ultrasonicate for 30 min to obtain a clear and transparent solution. Then let the solution stand to eliminate bubbles and obtain a precursor solution. The whole process should be carried out at below 10 °C to minimize the volatilization of DCM.

[0055] (2) The zinc sheet was cut into a size of 10*12 cm, and was grinded and polished with sandpaper of 2000, 3000, 5000 and 10000 respectively. Then, the surface-polished metal zinc was cleaned with deionized water, ethanol and acetone under ultrasonic conditions. The treatment temperature was 25°C and the treatment time was 30 min. After the treatment, it was dried in a vacuum drying oven at 80°C for 6 h to obtain a pure zinc negative electrode.

[0056] (3) Place the treated zinc sheet on a spin coater and spin coat the precursor solution on the treated zinc sheet; spin coating parameters: acceleration is 500 r / s 2 , the spin coating speed is 2000 r / s; the spin coating time is 30s.

[0057] After the spin coating was completed, the prepared sample was taken out and dried at 30°C in a vacuum for 12 h, and the piezoelectric protective layer (PLLA-BaTiO3@ZnS) was obtained on the pretreated zinc sheet.

[0058] Comparative Example 1 The zinc sheet was ground and polished with sandpaper of 2000, 3000, 5000 and 10000 respectively, and then the surface polished metal zinc was cleaned with deionized water, ethanol and acetone under ultrasonic conditions. The treatment temperature was 25°C and the treatment time was 30 minutes. After the treatment, it was dried in a vacuum drying oven at 80°C for 6 hours to obtain a pure zinc negative electrode (BareZn).

[0059] Embodiment 3: (1) A zinc symmetric battery was prepared by using the samples obtained in Example 1, Example 2 and Comparative Example 1 as the positive and negative electrodes, a solution containing 2M ZnSO4 as the electrolyte and glass fiber as the separator.

[0060] (2) Symmetrical battery charge and discharge tests were conducted at room temperature with a current density of 1 mAh / cm 2 The charge and discharge capacity of one cycle is 0.5 mAh / cm 2 .

[0061] In order to illustrate the relevant performance of the piezoelectric protective layer provided by the present invention, it is described in conjunction with the accompanying drawings.

[0062] from Figure 2 It can be seen that the surface uniformity and flatness of the left-handed polylactic acid-based zinc negative electrode protective layer containing BaTiO3 nanofillers with high piezoelectric properties prepared by electrospinning and spin coating are good, and the BaTiO3 nanofillers can be evenly distributed.

[0063] from Figure 3It can be seen that the zinc negative electrode protective layer prepared by electrospinning and spin coating does contain BaTiO3 nanofillers, which is consistent with the standard card peak position. The standard peak corresponding to PLLA has not been detected. The reason is that its crystallinity is not as good as that of BaTiO3 nanofillers and its content is relatively low.

[0064] from Figure 4 It can be seen that the prepared zinc negative electrode protective layer does have piezoelectric properties, and can output voltage under the action of pressure, thereby adjusting the electric field distribution.

[0065] from Figure 5 It can be seen that the zinc negative electrode protective layer with piezoelectric properties can reduce the corrosion of the electrolyte to the Zn-Zn symmetric battery, and the corrosion current is greatly reduced.

[0066] from Figure 6 It can be seen that the zinc negative electrode protective layer with piezoelectric properties can improve the cycle life of the Zn-Zn symmetric battery.

[0067] The present invention describes preferred embodiments and their effects. However, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0068] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a piezoelectric protective layer, characterized in that: The following steps are involved: The ester-terminated L-polylactic acid is dissolved in a dichloromethane solvent, and then a DMF solution and a BaTiO3 nanomaterial are added and mixed evenly to obtain a precursor solution; The precursor solution is evenly applied on the pretreated zinc sheet by electrostatic spinning or spin coating, and after drying, a piezoelectric protective layer is prepared on the pretreated zinc sheet.

2. The method for preparing a piezoelectric protective layer according to claim 1, characterized in that: The precursor solution is evenly applied to the pretreated zinc sheet by an electrostatic spinning method, including: using a conductive glue to stick the pretreated zinc sheet to an electrostatic spinning receiving roller, and then the precursor solution is electrostatically spun to obtain a piezoelectric protective layer on the pretreated zinc sheet.

3. The method for preparing a piezoelectric protective layer according to claim 2, characterized in that: The parameters during the electrospinning process include: the electrospinning syringe needle is connected to the positive electrode with a voltage of 15-20 kV; the receiving roller is connected to the negative electrode with a voltage of -8~-5kV; The distance between the needle tip and the receiving roller is 10-15 cm, the speed of the receiving roller is 120-150 r / min, the needle head moves left and right 80-120 mm, and the translation speed is 180-250 mm / min; The syringe containing the precursor solution was pushed at a speed of 0.1-0.2 mm / min; During the spinning process, the temperature is maintained at 10-15°C and the humidity is maintained at 20-50%.

4. The method for preparing a piezoelectric protective layer according to claim 1, characterized in that: The precursor solution is evenly applied on the pretreated zinc sheet by spin coating, and the spin coating parameters are acceleration of 400-600 r / s. 2 ; The spin coating speed is 1800-2000 r / s; The spin coating time is 20-40s.

5. The method for preparing a piezoelectric protective layer according to claim 1, characterized in that: The mass concentration of the ester-terminated L-polylactic acid in the precursor solution is 10-15%; the mass concentration of the BaTiO3 nanomaterial in the precursor solution is 5-10%.

6. The method for preparing a piezoelectric protective layer according to claim 1, characterized in that: The pre-treated zinc sheet comprises: grinding and polishing the zinc sheet with sandpaper of 2000, 3000, 5000 and 10000 meshes in sequence, and then cleaning the surface-polished metal zinc with deionized water, ethanol and acetone under ultrasonic conditions, respectively, at a treatment temperature of 20-25°C and a treatment time of 20-40 minutes. After the treatment, the zinc sheet is dried in a vacuum drying oven at 80-100°C for 5-8 hours to obtain the pre-treated zinc sheet.

7. A piezoelectric protective layer obtained by the method according to claims 1 to 6.

8. Use of the piezoelectric protective layer according to claim 7 on a zinc electrode.

9. A zinc negative electrode having a piezoelectric protective layer, characterized in that: The invention comprises a zinc sheet and a piezoelectric protective layer attached to the zinc sheet.

10. Use of the zinc negative electrode with a piezoelectric protective layer as claimed in claim 9 in a secondary zinc-based battery.

Citation Information

Patent Citations

  • Zinc negative electrode material with elastic protective layer, preparation and application thereof

    CN111600025A

  • Barium titanate nanowire-based aqueous zinc ion battery negative electrode material and preparation method thereof

    CN117352871A

  • L-polylactic acid coated beta-glycine composite fiber film as well as preparation method and application thereof

    CN118007314A

  • Apparatus for connecting reinforcing bars

    KR1020210138988A

  • Sheet containing nanofibers and method for producing same

    US20230085519A1